KONSEP DAN APLIKASI KEPEMIMPINAN PROFETIK - Munardji, Munardji (EDUKASI: Jurnal Pendidikan Islam, 2016)
The concept of prophetic leadership is basically a concept of leadership that is run by the Prophet and Messenger where in fact they are human just like his people, but they have the privilege and has properties which are noble and sublime in accordance with his position. Should the leaders in various institutions and levels must have and uphold the as-Siddiq (the truth), Amanah (Honesty), Tabligh (speak the truth and honesty as well Fathonah (intelligently manage institutions, human resources, natural resources and state assets. Similarly, leaders must be good examples in all asepek good life in society, nation and state.